The Relevance of God’s Voice in Conscience and Its Impact to Character Building - Laila Nabilahtauzzahro Ibrahim; Salsabila Nova Calista; Rommel Utungga Pasopati (Proceeding International Conference on Religion, Science and Education, 2023)
This article aims to assert how conscience works in line with God’s voice in human’s life. The condition of conscience is formless but speaks and guides human beings to truth. It will bring comfort if it is followed and will shape anxiety if being neglected. Religious reflection indicates that the thing that guides human beings is the voice of God himself. Somehow, conscience could be wrong, as it may not be mature enough to be followed by human beings. The problems continue with similarities and differences between human and God’s rationality if conscience is the voice of God. Ethics work in finite and mortal aspects while God is infinite and immortal. The main essence in connection between God’s voice and conscience is reflection that comes with matters of universality and particularity. By keep questioning, further considerations could be shaped besides merely saying no or nodding to conscience. Re-examination of human’s guidance to life should always be done to support further character building of human beings. This is due to character is not given but constructed by various fixed values and flexible understandings. Character should not find itself in total far right or left of human conscience and God’s voice. Human beings should always find balance in between by identifying meanings of profane and sacred values. In conclusion, existence of God’s voice in conscience is contestable as there will always be oppositions between worldly and spiritual matters. However, both of them could not be totally omitted and it is advantage of human’s rational character to consider those values as ultimate guidance to move forward.